Chiral pharmaceuticals: A review on their environmental occurrence and fate processes. (1st November 2017) - Sanganyado, Edmond; Lu, Zhijiang; Fu, Qiuguo; Schlenk, Daniel; Gan, Jay
Abstract: More than 50% of pharmaceuticals in current use are chiral compounds. Enantiomers of the same pharmaceutical have identical physicochemical properties, but may exhibit differences in pharmacokinetics, pharmacodynamics and toxicity. The advancement in separation and detection methods has made it possible to analyze trace amounts of chiral compounds in environmental media. As a result, interest on chiral analysis and evaluation of stereoselectivity in environmental occurrence, phase distribution and degradation of chiral pharmaceuticals has grown substantially in recent years. Here we review recent studies on the analysis, occurrence, and fate of chiral pharmaceuticals in engineered and natural environments. Monitoring studies have shown ubiquitous presence of chiral pharmaceuticals in wastewater, surface waters, sediments, and sludge, particularly β-receptor antagonists, analgesics, antifungals, and antidepressants. Selective sorption and microbial degradation have been demonstrated to result in enrichment of one enantiomer over the other. The changes in enantiomer composition may also be caused by biologically catalyzed chiral inversion. However, accurate evaluation of chiral pharmaceuticals as trace environmental pollutants is often hampered by the lack of identification of the stereoconfiguration of enantiomers. Furthermore, a systematic approach including occurrence, fate and transport in various environmental matrices is needed to minimize uncertainties in risk assessment of chiral pharmaceuticals as emerging environmental contaminants. Graphical abstract: Highlights: Critical review of environmental fate process of chiral pharmaceuticals. Summary of developments in chiral separation and detection of pharmaceuticals. Chiral inversion and sorption noted as critical in environmental fate. Studies on stereoselectivity in fate of pharmaceuticals in plants recommended.